Implementing a Circadian Adaptation Schedule after Eastward Flight in Young Male Athletes - Dean J. Miller (MDPI AG, 2021)
This study examined the effectiveness of a circadian adaptation schedule in male cricketers after an 8.5 h eastward time zone change. Ten participants (aged 18.7 ± 0.9 y) were randomly assigned to a control group or an intervention group. Participants in the intervention group followed a light exposure schedule in which they were instructed to seek light in the three hours preceding, and avoid light in the three hours following their estimated core body temperature minimum. The rate of adaptation was assessed using the nightly excretion rate of urinary 6-sulphatoxymelatonin (aMT6s). General linear mixed models were conducted to assess the effect of condition (i.e., control and light intervention) on nocturnal secretion of aMT6s. Significant main effects of day (F(7, 35) = 10.4, p < 0.001) were reflected by an increase in nocturnal melatonin excretion (i.e., all participants gradually adapted to the destination time zone). Subjective jet lag decreased by day (F(7, 54) = 22.9, p < 0.001), bedtime was delayed by day (F(7, 54) = 3.1, p = 0.007) and get up time was earlier by day (F(7, 35) = 5.4, p < 0.001). On average, it took 7 days for all participants to return to baseline levels following transmeridian travel. Similarly, it took 7 days for subjective jet lag to alleviate. In the initial 4 days of the protocol, the intervention group registered higher levels of nocturnal urinary melatonin, however, there was no significant differences in the rate of adaptation between the groups. It is possible that participants did not adhere to the intervention or that they followed the intervention but it was ineffective.